Polis und Metropolis im römischen Ägypten Städtisches Selbstverständnis in Hermupolis Magna - Free, Alexander (De Gruyter, 2024)
Even in pharaonic times, Hermupolis Magna was one of Middle Egypt's main regional centers. That did not change when the Romans became the land's new rulers, though they did not recognize Hermupolis as a fully-fledged city. However, under Roman rule, a development took place that resulted in Hermupolis being perceived as a polis throughout the Mediterranean. This study traces the path of that development
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Aug 2024)
Keywords: Antike; Mittelägypten; Papyrologie; Stadtentwicklung; HISTORY / Ancient / Greece; Polis; Römerzeit; Metropole; Selbstverständnis; Hermopolis Magna; Hochschulschrift